Sītā biḷāsa - Satyabādī Sāmantarāẏa, 19th cent (Utkaḷīẏa prācya granthamāḷā (Oḍiā) ;, 1977)
Narrative lyric poetry on Rāma, Hindu deity and Sītā; critically edited from manuscripts preserved in the Orissa State Museum.